Understanding financial services consumers and behavior - Harrison, Tina (Henry Stewart Talks, 2008)
Recent trends affecting the financial services consumer, The distinctive characteristics of financial services and their implications for consumer evaluation processes, The consumer decision process as it relates to financial services, Segment differences and the implications for consumer behavior and relationships